Chile : Decades of Educational Reform Deliver - Holm-Nielsen, Lauritz; Thorn, Kristian; Prawda, Juan (World Bank, Washington, DC, 2012)
A common vision and a consistent effort on the part of Chilean governments from the late 1960s to the present have placed Chile at an advanced stage of educational development. Today, primary education is almost universal, net secondary coverage is at 75 percent and more than one third of the 18- 24 age-cohort is enrolled in tertiary education. In addition, Chile features many components of a modern educational system, including a full school day, use of private providers, a competency-based curriculum, assessment of learning outcomes and a strong material basis for learning.